Antimutagenecity of twenty Philippine plants using the micronucleus test in mice - Lim - Sylianco, C.Y; Jocano, A.P; Lim, C.M (1988)
Methylmethanesulfonate, mitomycin C and dimethylnitrosamine are genotoxic to bone marrow cells, since they fragment the chromathin material leading to the formation of micronucleated polychromatic erythrocytes in bone marrow cells of experimental mice. Expressions from Persea americana Mill., Lagestroemia speciosa (L) Pers., Musa sapientum L., Dolichos lablab L., Achras zapota L., Imperata cylindrica L., Pseudelephantopus spicatus, Alstonia scholaris L., Eucalyptus deglupta Blume, Caesalpinia bonduc (L.) Roxb, Manihot esculenta Crantz, Sesbania grandiflora (L.) Pers., Artocarpus heterophyllus L., Pandanus odoratus Mus L., Rosmarinus officinale L., Ocimum sanctum L., Ricinus communis L., Cymbopogon citratus, Tectonia grandis L. reduced the induction of micronucleated polychromatic erythrocytes by methylmethanesulfonate, mitomycin C. and dimethylnitrosamine indicating that these plants have antimutagenic effects.